Comparison of how ambient PMc and PM2.5 influence the inflammatory potential. (December 2013) - Ferguson, Matthew D.; Migliaccio, Chris; Ward, Tony
Abstract Airborne particulate matter (PM) is one of the six criteria air pollutants currently regulated by the U.S. Environmental Protection Agency (EPA), with existing ambient standards for PM2.5 and PM10. Currently there are no health-based regulations for the size fraction between 2.5 and 10 µm, commonly known as the coarse fraction (PMc). The present study investigates current gaps in knowledge for PMc including exposure toxicity and PM ratios (PMc:PM2.5) in PM10. Throughout the world, all the three PM size fractions have been shown to be associated with adverse impacts. Recent studies have shown that PMc can be more detrimental to susceptible populations when directly compared to PM2.5, and that the PMc fraction in PM10 can account for the majority of the inflammatory response from PM10 exposure. In our studies we utilized a bone marrow-derived mouse macrophage in vitro system to compare the inflammatory potential of PMc, PM2.5 and mixtures of the two. The result was a linear increase in interleukin(IL) -1β with increasing levels of exposure to winter and summer PMc, as compared to PM2.5, which exhibited logarithmic growth. Also, exposure to PM10 as a function of PM2.5 and PMc mass ratios showed that IL-1β and TNF-α levels increased synergistically with a greater burden of PMc. Endotoxin content in the PM did not correlate with these results, suggesting that other activators in PMc are likely responsible for activating the NF-κB pathway and the inflammasome.